Implementasi Active Learning Tipe Everyone Is A Teacher Here Dalam Meningkatkan Hasil Belajar Siswa - Agus Dwi Santosa; Azzahida Devi Izdaharo (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Active Learning Tipe Everyone Is A Teacher Here is one of the active learning strategies used to increase students' courage to ask questions. The Moral theology teacher for class VII MTs Sunan Drajat applies this strategy in the hope that it can liven up the learning atmosphere, learning is not only focused on the teacher (Teacher Centered Learning), students are also children who dare to express their opinions in class, and later can improve student learning outcomes. on the subject of Moral theology in class VII MTs Sunan Drajat Sugio Lamongan. The research method that the researcher uses here is a qualitative research method with data collection techniques through field studies which include observation, interviews and documentation which shows the results of the study that the implementation of the Active Learning Type Everyone Is A Teacher Here strategy can improve the learning outcomes of class VII students on subjects Moral theology at MTs Sunan Drajat Sugio, Lamongan Regency and students also become more daring to ask questions and express their opinions in learning Moral theology